Hubungan Dukungan Keluarga dengan Konsep Diri Pasien Stroke di Rumah Sakit Santa Elisabeth Medan Tahun 2024 - Lindawati F. Tampubolon; Lili S. Tumanggor; Asni Marida Hulu (Lembaga Pengembangan Kinerja Dosen, 2025)
Stroke is a neurological condition characterized by sudden focal injury to the central nervous system due to cerebral infarction, intracerebral hemorrhage, or subarachnoid hemorrhage. In addition to the physical impact, stroke patients also experience psychological changes in the form of limited movement, communication, and thinking skills that can interfere with role functions and reduce self-esteem. This decrease in self-esteem has the potential to cause self-concept disorders, so family support is an important factor in helping patients accept the condition and maintain hope. This study aims to analyze the relationship between family support and self-concept in stroke patients at Santa Elisabeth Hospital Medan in 2024. The study used a quantitative design with a cross sectional approach and involved 42 respondents who were selected through a total sampling technique. Data collection was carried out using family support questionnaires and self-concept questionnaires. The results showed that most of the respondents had high-category family support (64.3%) and positive self-concept (83.3%). The Spearman Rank statistical test showed a significant relationship between family support and self-concept (p = 0.001) with a correlation coefficient value of 0.552 indicating a positive relationship with very strong strength. This study emphasizes the importance of family support in helping stroke patients accept changes in body functions and build a more adaptive self-concept.